Analisis Kualitas Pelayanan, Kualitas Produk dan Harga Terhadap Kepuasan Konsumen Fachira Laundry Sungai Raya dalam Pontianak Tenggara - Zen, Muhammad; Firayanti, Yuni; Marhamah, Marhamah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the influence of service quality, product quality, and price on customer satisfaction at Fachira Laundry Sungai Raya Dalam, Southeast Pontianak. The background of this study is based on the increasing competition in the laundry service business, so that every service provider is required to be able to maintain service quality, provide quality laundry results, and set appropriate prices to maintain customer satisfaction. The research method used is a quantitative approach with multiple linear regression analysis techniques. A sample of 100 respondents was obtained through convenience sampling techniques. The research data was processed with the help of SPSS version 20 through validity, reliability, classical assumption tests, and partial (t-test) and simultaneous (F-test) tests. The results of the study indicate that simultaneously the variables of service quality, product quality, and price have a significant effect on customer satisfaction, with a coefficient of determination (R²) of 64.1%. This means that the three variables together are able to explain the variation in customer satisfaction by 64.1%, while the rest is explained by other factors outside this study. Meanwhile, partially the service quality variable does not have a significant effect on customer satisfaction. In contrast, the product quality and price variables have a positive and significant effect on customer satisfaction. This confirms that Fachira Laundry's customer satisfaction is more determined by the quality of the laundry and the appropriateness of the price offered than by the service aspect. The implication of this research is the need for Fachira Laundry to improve the quality of its laundry and maintain a price balance with the benefits received by consumers, so that customer satisfaction and loyalty can be maintained.